PEMERIKSAAN PENYARING KADAR GULA DARAH SEBAGAI UPAYA DETEKSI DINI DIABETES MELITUS - Yanuar Primanda; Ferika Indarwati (Universitas Muhammadiyah Yogyakarta, 2018)
Diabetes mellitus (DM) is one of serious health problems worldwide including in Indonesia. Early detection and screening for DM is beneficial to prevent the development of DM. Unfortunately, early screenings of DM are rarely done by communities (particularly elder adults) in Indonesia. Lack of knowledge of early screening of DM and minimum facilities influenced this phenomenon. Therefore, this project was aimed to help community in Ranting Muhammadiyah and Aisyiyah Tamantirto Selatan to detect early onset of DM. This project was integrated with a social program held by the Ranting Muhammadiyah and Aisyiyah Tamantirto Selatan. There were five steps of the screening program namely spirituality supports, moderate exercises, glucose screenings, physical assessments and drug prescriptions, and health educations. Overall 263 people voluntarily participated in this project and 219 of them finished the screening program. Most of the participants was female, aged from 41-60 years. Blood glucose screening showed that 3.2% had low blood glucose level (<60 mg/dl), 57.3% had normal blood glocose level (60-140 mg/dl), 22.5% had random blood glucose 140-200 mg/dl which categorized as pre DM and almost 20% had random blood glucose more than 200 mg/dl which categorized as DM. Screening and early detection is important for people to prevent DM and implement measures to delay the complecations among people with DM